Fabrication of MnOx-CeO2/cordierite catalysts doped with FeOx and CuO for preferable catalytic oxidation of chlorobenzene. Issue 13 (6th June 2020) - Huang, Qiong; Si, Han; Yu, Shukun; Wang, Jiaxiao; Tao, Tao; Yang, Bo; Zhao, Yunxia; Chen, Mindong
ABSTRACT: A series of MnOx -CeO2 catalysts with MOx doping (M = Cu, Fe, Co and La) supported on cordierite were synthesized by the citric acid complex method, showing preferable catalytic oxidation of chlorobenzene. The distribution of active oxides, surface areas, as well as the structural morphology of M-MnOx -CeO2 catalysts varied with the different Mn/Ce and M/Mn molar ratios. Meanwhile, physicochemical properties of these catalysts were characterized by XRD, BET, SEM, TEM, H2 -TPR and IR. More importantly, the catalytic oxidation routes were also investigated where the process was from chlorobenzene to CO2, H2 O, HCl and other by-products for the FeOx -MnOx -CeO2 and CuO-MnOx -CeO2 catalysts. The CuO-MnOx -CeO2 catalysts showed a higher chlorobenzene conversion, and the measured light-off temperature T 90 was approximately 400°C. However, a large amount of chloropropane as main by-products was observed. For the FeOx -MnOx -CeO2 catalysts, more carbon monoxide could be found with inadequate oxidation. Comparative analyses of two catalysts indicated that the main cause of the oxidation activities and mechanisms were different in the oxidation capacity and water absorbability of FeOx and CuO. Nevertheless, all of these catalysts did not exhibit any deactivation due to chloride with a high reaction temperature, with chloride transformed to form HCl in the off-gas stream. GRAPHICAL ABSTRACT: